Metabolic Profiles of the Gut Microbiota in Patients with Different Stages of Metabolism Dysfunction-Associated Fatty Liver Disease - X. Cao; O. Yu. Zolnikova; R. V. Maslennikov; E. A. Poluektova; E. L. Bueverova; M. S. Reshetova; M. S. Zharkova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to study the metabolic activity of the intestinal microbiota depending on the stage of metabolic dysfunction-associated fatty liver disease (MAFLD).   Materials and methods. The study included 85 patients with MAFLD (27 patients with steatosis without steatohepatitis and fibrosis, 42 patients with steatohepatitis, 16 patients with cirrhosis as an outcome of MAFLD, Child — Pugh class A–B) and 20 healthy people who formed the control group. The level and spectrum of short-chain fatty acids (SCFA) were determined by gas-liquid chromatography.   Results. It was found that patients with MAFLD at the stage of steatosis and cirrhosis of the liver have unidirectional changes in the metabolic activity of the intestinal microbiota. We established a decrease in the absolute concentrations of SCFA — their total content, the level of acetate, propionate, butyrate, a decrease in the level of isoacids. The SCFA profiles showed an increase in the proportion of acetate and a decrease in propionate and butyrate. Moreover, changes in the named parameters of SCFAs are aggravated with progression to liver cirrhosis. At the stage of steatohepatitis, we identified two subgroups of patients with different levels of metabolic activity of the microbiota. Patients whose microbiota metabolism for SCFA production was high had correspondingly elevated SCFA levels. And, on the contrary, patients in whom the metabolic activity of the microbiota was reduced were characterized by a steady decrease in SCFAs and disease progression to liver cirrhosis. In the study, we showed an inverse correlation between the calculated prognostic indices of NFS and FIB-4, elastography values with the total level of SCFA, the level of acetate, propionate, butyrate. Thus, a decrease in the content of SCFA for patients with MAFLD can be considered as a prognostic marker of an unfavorable course of liver disease.